2010年代におけるオーストラリア-南極海盆の南極底層水の淡水化傾向の反転 - Aoki, Shigeru; Yamazaki, Kaihe; Hirano, Daisuke; Katsumata, Katsurou; Shimada, Keishi; Kitade, Yujiro; Sasaki, Yuko; Murase, Hiroto (Scientific Reports, 2020)
The Antarctic continental margin supplies the densest bottom water to the global abyss. From the late twentieth century, an acceleration in the long-term freshening of Antarctic Bottom Waters (AABW) has been detected in the Australian-Antarctic Basin. Our latest hydrographic observations reveal that, in the late 2010s, the freshening trend has reversed broadly over the continental slope. Near-bottom salinities in 2018–2019 were higher than during 2011–2015. Along 170° E, the salinity increase between 2011 and 2018 was greater than that observed in the west. The layer thickness of the densest AABW increased during the 2010s, suggesting that the Ross Sea Bottom Water intensification was a major source of the salinity increase. Freshwater content on the continental slope decreased at a rate of 58 ± 37 Gt/a in the near-bottom layer. The decadal change is very likely due to changes in Ross Sea shelf water attributable to a decrease in meltwater from West Antarctic ice shelves for the corresponding period. journal article